2012
DOI: 10.1007/s00192-012-1840-x
|View full text |Cite
|
Sign up to set email alerts
|

One-year results of a prospective randomized, evaluator-blinded, multicenter study comparing TVT and TVT Secur

Abstract: One-year results of a prospective randomized, evaluator-blinded, multicenter study comparing TVT and TVT Secur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Outcomes in women randomized to RP MUS and SIMS procedures were compiled in a recent Cochrane systematic review and meta‐analysis, and a 2017 update revealed no additional comparisons . Five trials compared the bottom‐to‐top RP MUS with various SIMS . Women were more likely to remain incontinent after SIMS than after RP MUS (41% vs 26%; RR 2.08; 95%CI 1.04‐4.14) and SIMS were associated with a higher risk of de novo urgency (RR 2.39; 95%CI 1.25‐4.56).…”
Section: Retropubic (Rp) Approachmentioning
confidence: 99%
“…Outcomes in women randomized to RP MUS and SIMS procedures were compiled in a recent Cochrane systematic review and meta‐analysis, and a 2017 update revealed no additional comparisons . Five trials compared the bottom‐to‐top RP MUS with various SIMS . Women were more likely to remain incontinent after SIMS than after RP MUS (41% vs 26%; RR 2.08; 95%CI 1.04‐4.14) and SIMS were associated with a higher risk of de novo urgency (RR 2.39; 95%CI 1.25‐4.56).…”
Section: Retropubic (Rp) Approachmentioning
confidence: 99%
“…One other published randomized trial compared TVT Secur (using the hammock (H) technique that places the tape in a position replicating an obturator tape) to TVT, recruiting 125 women, less than half of the planned 280 patients [ 19 , 20 ]. Recruitment was stopped early because of a significantly lower cure rate at 2 months, and concern about three severe adverse events in the TVT Secur group (a tape erosion into the urethra, a tape placed inside the bladder, and bleeding from the corona mortis) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher complication rate of the TVT procedure made most surgeons wonder whether a new, ‘safer’ variant (TVT‐Secur™) can be preferred, over the older procedure. However, in a recent multicentre study comparing TVT and TVT‐Secur™, the latter was linked to a higher rate of serious complications, one of which was postoperative bleeding due to injury of the corona mortis …”
Section: Discussionmentioning
confidence: 99%
“…This operation has given way to new, minimally invasive procedures, such as the TVT sling (introduced in 1998), the TOT sling (2002) and, finally, the TVT‐Secur™ (2006). However, these new methods are not free of complications, but have been linked to corona mortis – and in general, vessel – injury …”
Section: Introductionmentioning
confidence: 99%